2021
DOI: 10.1158/0008-5472.can-20-1713
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA VESTAR Regulates Lymphangiogenesis and Lymph Node Metastasis of Esophageal Squamous Cell Carcinoma by Enhancing VEGFC mRNA Stability

Abstract: Lymph node metastasis is one of the most malignant clinical features in patients with esophageal squamous cell carcinoma (ESCC). Understanding the mechanism of lymph node metastasis will provide treatment strategies for patients with ESCC. Long noncoding RNAs (lncRNA) play a critical role in the development and progression of human cancers. However, the role and mechanism of lncRNAs in lymph node metastasis remain largely unknown. Here we show that VEGFC mRNA stability–associated long noncoding RNA (VESTAR) is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…As HuR is crucial for mRNA stability [ 27 ] and plays an oncogenic role in cancers [ 28 , 29 ], and GLUD1 mRNA and protein levels were down-regulated by HuR knockdown in this study (Fig. 5G, H ), we further explored the stability of GLUD1 mRNA by HuR knockdown followed by ACTD treatment, and found that the stability of GLUD1 mRNA was decreased in the SiHa and CaSki cells with HuR knockdown, compared with control cells (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…As HuR is crucial for mRNA stability [ 27 ] and plays an oncogenic role in cancers [ 28 , 29 ], and GLUD1 mRNA and protein levels were down-regulated by HuR knockdown in this study (Fig. 5G, H ), we further explored the stability of GLUD1 mRNA by HuR knockdown followed by ACTD treatment, and found that the stability of GLUD1 mRNA was decreased in the SiHa and CaSki cells with HuR knockdown, compared with control cells (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…VESTAR interacts with HuR to promote the binding of HuR to VEGF-C mRNA. Therefore, VESTAR -mediated VEGF-C mRNA stability may be an important contributor to lymph node metastasis in ESCC and could be a novel target for the diagnosis and treatment of tumor metastasis ( 42 ).…”
Section: Long-chain Non-coding Rnas Promote the Occurrence And Develo...mentioning
confidence: 99%
“…Esophageal carcinoma (EC) is one of the most malignant tumors worldwide, and present a great threat to the health of society [ 1 , 2 ]. EC is well known by its high rate of metastasis, aggressive invasion and poor prognosis [ 3 ]. Surgery and chemotherapy are effective treatments for EC diagnosed at an early stage, while a lot of EC patients comes to recurrence or metastasis, and eventually develop to advanced stages of cancers, which present poor prognosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%